Molecular-phylogenetic analyses of Ixodes species from South Africa suggest an African origin of bird-associated exophilic ticks (subgenus Trichotoixodes) - (:unkn) unknown (My University, 2023)
Background Among hard ticks (Acari: Ixodidae), the genus Ixodes comprises the highest number of species, which in turn are most numerous in the Afrotropical zoogeographic region. In South Africa extensive morphological studies have been performed on Ixodes species but only few reports included molecular analyses. MethodsIn this study, 58 Ixodes spp. ticks, collected from ten mammalian and eight avian host species in South Africa, were molecularly and phylogenetically analyzed. In addition, a newly collected sample of the Palearctic Ixodes trianguliceps was included in the analyses. Results Among the ticks from South Africa, 11 species were identified morphologically. The majority of ticks from mammals represented the Ixodes pilosus group with two species ( n = 20), followed by ticks resembling Ixodes rubicundus ( n = 18) and Ixodes alluaudi ( n = 3). In addition, single specimens of Ixodes rhabdomysae , Ixodes ugandanus , Ixodes nairobiensis and Ixodes simplex were also found. Considering bird-infesting ticks, Ixodes theilerae ( n = 7), Ixodes uriae ( n = 4) and ticks most similar to Ixodes daveyi (provisionally named I. cf. daveyi , n = 2) were identified. Molecular analyses confirmed two species in the I. pilosus group and a new species ( I. cf. rubicundus ) closely related to I. rubicundus sensu stricto. Phylogenetic trees based on concatenated mitochondrial or mitochondrial and nuclear gene sequences indicated that the subgenus Afrixodes forms a monophyletic clade with bird-associated exophilic ticks (subgenus Trichotoixodes ). Ixodes trianguliceps clustered separately whereas I. alluaudi with their morphologically assigned subgenus, Exopalpiger . Conclusions Phylogenetic analyses shed new lights on the relationships of Ixodes subgenera when including multiple sequences from subgenus Afrixodes and African as well as Palearctic species of subgenera Trichotoixodes and Exopalpiger . Subgenera Afrixodes and bird-associated Trichotoixodes sh
Keywords: African Research